The Teacher Assessment of the Feasibility of Presenting the Teaching Module for Writing Explanatory Texts Using Project-Based Learning - Triyono, Andri; Ristiani, Iis (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
There is one teaching module unit for reading skills in explanatory texts for Grade 5 at State Elementary School. The teaching module was developed using the project-based learning model. The teaching module has been used for a long time by grade 5 teachers of State Elementary School. A good teaching module must have four eligibility requirements, including presentation eligibility. This study aims to describe the results of teacher assessments of the presentation eligibility of the teaching module for writing skills in explanatory texts, developed using Project-Based Learning for grade 5 students at State Elementary School. This research was conducted during the odd semester of the 2024/2025 academic year at State Elementary School. The method used in this study is a descriptive-quantitative approach. The subjects of the study were three senior class teachers of Budiasih State Elementary School. Data on teacher assessments of the presentation eligibility of the teaching module for writing skills in explanatory texts, developed using Project-Based Learning for grade 5 at State Elementary School, were collected using a closed questionnaire with four options that were arranged systematically and objectively, ensuring content validity. The four options in this questionnaire are a simplification of the Likert scale. The data were analyzed using descriptive statistical procedures using a tabulation system. The results of the study showed that the teacher's assessment of the feasibility of presenting the teaching module for developing writing explanatory text skills using Project-Based Learning for grade 5 students at State Elementary School was categorized as good.